Prawne i polityczne konsekwencje wyroku Trybunału Sprawiedliwości z dnia 6 września 2017 roku w sprawie Republiki Słowackiej i Węgier przeciwko Radzie Unii Europejskiej w przedmiocie skargi o stwierdzenie nieważności decyzji (UE) 2015/1601 (Politeja, 2024)
LEGAL AND POLITICAL CONSEQUENCES OF THE JUDGMENT OF THE COURT OF JUSTICE OF 6 SEPTEMBER 2017 IN THE CASE OF THE SLOVAK REPUBLIC AND HUNGARY V COUNCIL OF THE EUROPEAN UNION ON THE ACTION FOR ANNULMENT OF DECISION (EU) 2015/1601The subject of the paper is the analysis of the judgment of the Court of Justice in joined cases C-643/15 and C-647/15 annulment of Council Decision (EU) 2015/1601 of 22.09.2015 establishing provisional measures in the area of international protection for the benefit of Italy and Greece. The Republic of Poland intervenes in the allegations raised in the complaint against the Council of the EU. The study will present the context, genesis and content of the contested decision, as well as the arguments of the parties and the assessment of individual allegations by the Court. The decision was taken in response to the migration crisis in the Mediterranean, which prompted the EU institutions to take solidarity measures in favour of frontline countries. The decision provides, e.g., for the relocation of persons who have applied for international protection from Italy and Greece to the territory of other Member States. The aim of the paper is to examine the impact of the judgment of the Court of Justice on the shape of immigration policy manifested in the practice of EU Member States and EU institutions. The study mainly uses the legalanalytical method. Selected acts of primary and secondary EU law and judgments of the Court of Justice were subjected to legal analysis.